Legal Analysis of the Constitutional Court’s Decision on Campaign Regulations in Schools and Universities - Diana Nur Mc Nuff; Sulaksono Sulaksono (Universitas Negeri Surabaya, 2025)
This research aims to investigate the practice regarding the process of application. August 15, 2023, became a historic day for Indonesia with the approval of the Constitutional Court's Decision, allowing campaigning in educational institutions. The proposal to amend Constitutional Court Decision Number 65/PUU-XXI/2023 was first submitted by Ong Yenny and Handrey Mantiri, members of the Jakarta Regional People's Representative Council. This research falls under the category of normative juridical research, also known as conceptual and legal approaches. Normative juridical research is conducted by examining secondary sources such as literature and regulations related to the researched issue. According to the petitioner, the Constitutional Court Decision Number 65/PUU-XXI/2023 contradicts Law Number 7 of 2017, specifically Article 280 paragraph (1) letter h and its explanation. There are two different provisions in the law, which have resulted in legal norms becoming uncertain. The main issue with Article 280 paragraph (1) letter h of Law Number 7 of 2017 is not based on norm conflict, but rather on differences in law enforcement, leading to injustice in the conduct of elections. The primary purpose of elections is to provide an opportunity for Indonesian citizens to express their aspirations and choose their preferred leaders to represent them in government. Elections are a means of upholding popular sovereignty based on democratic values. The Constitutional Court's decision not only limits the role of campuses in educating future generations but also enhances Indonesia's democracy by helping to create voters who make decisions based on logical reasoning and facts.